Data-Driven Decision Making in Fragile Contexts : Evidence from Sudan - Hamilton, Alexander; Hammer, Craig (Washington, DC: World Bank, 2017)
Data deficiencies contribute to state fragility and exacerbate fragile states’ already limited capacity to provide basic services, public security and rule of law. The lack of robust, good quality data can also have a disabling effect on government efforts to manage political conflict, and indeed can worsen conflict, since violent settings pose substantial challenges to knowledge generation, capture and application. In short, in fragile contexts the need for reliable evidence at all levels is perhaps greater than anywhere else.